Pengaruh Corporate Social Responsibility (CSR) dan Motivasi Terhadap Kinerja Karyawan pada PT Taruma Jaya Utama - Abizachryan Akbar; Sungkono (PENG: Jurnal Ekonomi dan Manajemen, 2024)
The aim of this research is to investigate in more depth the influence of Corporate Social Responsibility (CSR) in motivation on operational performance at PT Talrumal Jalyal Utalmal. By identifying the relationship between a company’s CSR practices and its internal motivation, as well as its interrelationships with its individual performance factors, this research aims to provide a valuable analysis of how a company’s management can manage effective strategies to improve its performance in Kalryalwaln, as well as strengthening the positive contribution of halaln searches to Malsyalralkalt in the surrounding environment. Based on the results of the research, social responsibility has a significant positive influence on the performance of PT Talrumal Jalyal Utalmal’s supervisory staff, with the value proven by the value sig 0l,0l0l0l< α (0l,0l5) in tcount (12.0l48) > ttalbel (0 l.67 9 ) from the tally. Based on the research results, the value is proven by the value sig 0l,0l0l4 < α (0l,0l5) in tcount (1.764) > ttalbel (0l.679) in ttal bell.